Nivel de vulnerabilidad a los desastres por movimientos sísmicos en las instituciones educativas del distrito de Salaverry - Valderrama Cruz, Cecilia (2016)
This research study descriptive, prospective cross-sectional, was performed in the district of Salaverry, aimed to determine the level of vulnerability to disasters by earthquakes of Educational Institutions. The sample consisted of 12 schools that met the inclusion criteria. Data were collected using a questionnaire called "threat vulnerability analysis Earthquake", the data collected were processed using the SPSS 20 program reliability through a pilot study. In making the overall classification, it was found that 33.4% of educational institutions were highly vulnerable, 50% of which corresponded to medium-high vulnerability, low vulnerability to 8.3% and 8.3% Minimum vulnerability. In addition the level of vulnerability to disasters by earthquakes predominantly in private educational institutions was medium-high, on state was high, so does the level of overall vulnerability was predominantly upper middle.